Characterization of a barley (Hordeum vulgare L.) mutant with multiple stem nodes and spikes and dwarf (msnsd) and fine-mapping of its causal gene - Qin, Dandan D.; Liu, Rui; Xu, Fuchao; Dong, Guoqing; Xu, Qing; Peng, Yanchun; Xu, Le; Cheng, Hongna; Guo, Ganggang; Dong, Jing; Li, Chengdao (Frontiers in Plant Science, 2023)
Introduction Multiple nodes and dwarf mutants in barley are a valuable resource for identifying genes that control shoot branching, vegetative growth and development. Methods In this study, physiological, microscopic and genetic analysis were conducted to characterize and fine-map the underling gene of a barley mutant with Multiple Stem Nodes and Spikes and Dwarf (msnsd), which was selected from EMS- and 60Co-treated barley cv. Edamai 934. Results and discussion The msnsd mutant had more stem nodes, lower plant height and a shorter plastochron than Edamai 934. Moreover, the mutant had two or more spikes on each tiller. Microscopic analysis showed that the dwarf phenotype of msnsd resulted from reduced cell lengths and cell numbers in the stem. Further physiological analysis showed that msnsd was GA3-deficient, with its plant height increasing after external GA3 application. Genetic analysis revealed that a single recessive nuclear gene, namely, HvMSNSD, controlled the msnsd phenotype. Using a segregating population derived from Harrington and the msnsd mutant, HvMSNSD was fine-mapped on chromosome 5H in a 200 kb interval using bulked segregant analysis (BSA) coupled with RNA-sequencing (BSR-seq), with a C-T substitution in the exon of HvTCP25 co-segregating with the msnsd phenotype. RNA-seq analysis showed that a gene encoding gibberellin 2-oxidase 8, a negative regulator of GA biosynthesis, was upregulated in the msnsd mutant. Several known genes related to inflorescence development that were also upregulated and enriched in the msnsd mutant. Collectively, we propose that HvMSNSD regulates the plastochron and morphology of reproductive organs, likely by coordinating GA homeostasis and changed expression of floral development related genes in barley. This study offers valuable insights into the molecular regulation of barley plant architecture and inflorescence development.